The principles of oncological alertness at the outpatient therapeutic stage - A. S. Sycheva; A. L. Kebina; A. V. Nosova; A. L. Vertkin (Лечащий Врач, 2021)
Objective of the study is an increasing the detection rate of oncological diseases in the early stages using questionnaires. The study involved 25,467 patients who came to an appointment with a general practitioner/general practitioner for any request. During the study, primary care physicians, regardless of the purpose of the visit, purposefully asked questions regarding the risks of malignant neoplasms. The detection rate of oncological diseases was 60,4% in the first half of 2018 against 56,3% in the same period of 2017. In accordance with specific localizations, the following results were obtained: detection of stomach cancer increased by 3%, colon cancer by 2%, malignant neoplasms of the trachea, bronchi and lungs increased by 6%, and the mammary gland, cervix and prostate increased by 1%, 8%, and 2%, respectively. The presence of a clear stereotype of oncological alertness in the primary care physician may contribute to a decrease in the number of advanced stages of tumors due to the initiation of specialized treatment at earlier stages. In such a situation, the main task of the therapist and general practitioner is to identify suspicious symptoms of malignant neoplasms using an algorithmized approach and refer the patient to a specialized institution.